Eric Carle's dragons dragons & other creatures that never were - Carle, Eric; Whipple, Laura (New York Puffin Books, 2004)
An illustrated collection of poems about dragons and other fantastic creatures by a variety of authors.
"All ages."
Keywords: Animals, Mythical -- Juvenile poetry; Animals, Mythical -- Poetry; Poetry -- Collections